Horror Journalism Practices in Jurnalrisa - Nur Amala Saputri (CHANNEL: Jurnal Komunikasi, 2021)
The presence of Youtube as a new media has opened up opportunities for alternative journalism practices. Basically, horror journalism is a form of alternative journalism that has emerged as an effort to fight against mainstream journalism in the mass media. This research focuses on how the representation of horror journalism practices in the Jurnalrisa Youtube channel. Researchers chose 3 video titles for Jurnalrisa in 2020 as research objects, namely Jurnalrisa #81 – Jurit Malam, #tanyarisa – #TANYAPETERCS, and Jurnal Cerita Misteri #6 – Peter CS Pernah Datang Ke Rumah Reza di Belanda! The three of them were chosen based on the number of levels of audience popularity that was obtained. The method used is textual analysis using the genetic structuralism theory of Pierre Bourdieu. This research shows that there are 3 new forms of horror journalism practice carried out by Jurnalrisa, namely interviews, mediumizing ghosts, and conducting virtual search investigations to discuss mystical and creepy events in a video sent by netizens to Jurnalrisa. The practice of investigations in the Mystery Story Journal is a novelty presented by Jurnalrisa by involving netizens as reporters or reporters of events. Through these efforts, Jurnalrisa presents a discourse that ghosts are not completely bad, evil, and negative, which is represented by the ghost of Karuhun, where he is presented as an active "subject" and becomes a form of historical evidence for events that occurred in the past.